Semiochemicals for Sustainable Agriculture - Jayanthi, P D Kamala (Indian Journal of Plant Protection, 2025)
The changing climatic conditions and extensive monocropping have influenced the ecology and biology of insect pests leading to a considerable shift in their pest status across several crops posing challenges to farmers and researchers alike. The increasing complexity of pest management in agricultural/horticultural crop ecosystems stresses the need for sustainable pest management strategies which advocate the use of natural processes and mechanisms against insect pests. Considering the recent global emphasis on sustainable pest management solutions with minimal ‘carbon footprinting’, intensive efforts are being made to identify green chemicals that can support IPM strategies with minimal disturbance to agri-ecosystems. In this context, the dependency of insects on chemical cues to locate their hosts and mates offers a tremendous opportunity to identify potential ‘behaviour modifying chemicals’ (= semiochemicals, infochemicals) that can be exploited for their management. Studies have established that herbivore-induced plant volatiles (HIPVs) are attractive to predators and parasitoids during the initial stages of insect attack and provide timely control of pests. Therefore, a thorough understanding of the chemical mediated communication among the insect pests with their hosts, conspecifics and natural enemies helps to identify weak behavioural links that can be manipulated across the trophic interactions. Further, insects and plants are constantly interacting with endosymbionts/microorganisms that also exert their influence on trophic interactions. Gut-associated endosymbiont volatiles also have direct behavioural effects on herbivores; volatiles of Klebsiella oxytoca, an endosymbiont of female Oriental fruit fly, Bactrocera dorsalis attracted male conspecifics in our studies. Learning the chemical language of plants-insect pests and their natural enemies in an agro-ecosystem elucidates the role and origin of semiochemicals that are crucial in insect-plant interactions and helps to locate the trophic level at which they are active. This will aid to formulate end-to-end pest management programs and bring out viable behavioural cues that can be incorporated into current IPM programs However, in order to understand/manipulate/modulate the various behaviour-modifying chemicals that are being deployed by insects and to maximize their usefulness to make insect pests vulnerable, collaborations among biology, chemical ecology, physiology and analytical chemistry are of paramount importance.